Implications of the goods and services tax on business - Fok, Teen Ngai (2014)
The introduction of the Goods and Services Tax (GST on the lst of April 1994, is part of a new fiscal policy aiming to make Singapore more competitive. The effects of GST are highly pervasive. Knowledge of the implications of GST on businesses not only helps GST-registered businesses cope with GST better, but may also help non-registered businesses decide on whether they want to register voluntarily. A three-prong approach was used to ensure that various implications are investigated. Literature reviews and brainstorming sessions were conducted before an empirical study was conducted at Provisions Suppliers Corporation (PSC), a company listed on the Stock Exchange of Singapore. PSC's core activities are the distribution of provision supplies and the operation of the Econ-Minimart franchise. This empirical study provides valuable insight into the implementation process of GST. Some of the issues businesses may expect to encounter include effects on cash flow and the need to modify the accounting system. Critical success factors such as adequate training of employees and top management involvement are also highlighted. A framework for planning and organising the implementation of GST is also provided to help businesses which are contemplating registration for GST.